Integrasi Pendidikan Berwirausaha dan Total Quality Management untuk Pendidikan yang Efektif dan Unggul - Wulandari, Tyas; Timan, Agus; Sumarsono, Raden Bambang (Proceedings Series of Educational Studies, 2025)
Schools that integrate entrepreneurship education are educational institutions that not only focus on delivering an academic curriculum, but also encourage their students to develop entrepreneurial skills, an entrepreneurial spirit and an innovative attitude in working. The effective school assessment model is one of the instruments that education managers hope to use to determine the level of success of each school. The results of this assessment can then be used as consideration for making efforts to improve the school. Schools that have a good, transparent and accountable management system, and are able to empower every important component of the school,both internally and externally, in order to achieve the school's vision, mission and goals effectively and efficiently. This research aims to describe entrepreneurship education using total quality management to achieve effective and superior schools. The method used in this research is descriptive qualitative. Data collection techniques use literacy studies and interview tests. The research subjects are entrepreneurship teachers, fashion designers. and Class